Effective treatment of textile industry wastewater by combined ultraviolet assisted and Fe2+ catalyzed percarbonate oxidation - Unal Yilmaz, Ezgi; Gundogdu, Hilal; Bilgin, Oyku Nur; Yokus, Senem; Turk, Oruc Kaan; Yazici Guvenc, Senem; Can-Guven, Emine; Varank, Gamze (TAYLOR & FRANCIS INC, 2024)
Sustainable water management is very important for industries with high water consumption and wastewater generation, such as the textile industry. This study aims to investigate the treatment of textile wastewater with ultraviolet (UV) assisted and Fe2+ catalyzed sodium percarbonate (SPC) oxidation, which is an eco-friendly treatment method in terms of both added oxidant and activation methods. Based on the removal efficiencies and reaction rates, a sorting was made as UV/SPC/Fe2+ > SPC/Fe2+ > UV/Fe2+ > UV/SPC > SPC > UV. It was observed that the removal efficiencies increased as the SPC dose increased, and decreased due to the scavenging effect with the 5 g/L oxidant dose, and the optimum SPC dose was determined as 2.5 g/L. It was determined that the removal efficiencies were higher in acidic conditions and high UV power applications. Under optimum operating conditions (pH:3, SPC dose: 2.5 g/L, Fe2+ dose: 1 g/L, UV lamps: 4), 68% COD, 80.9% UV254, and 92% color removal were achieved. Under optimum conditions energy cost, chemical cost, and operational cost were calculated as 11.9 $/m(3), 0.20 $/m(3,) and 12.1 $/m(3), respectively. By reducing the process COD concentration to 236.2 mg/L, discharge standards have been achieved, and the applicability of the UV/SPC/Fe2+ process was proven.
Keywords: Sodium percarbonate; photo-fenton; textile wastewater; zero liquid discharge; sustainable treatment; AQUEOUS-SOLUTION; FENTON PROCESS; DEGRADATION; REMOVAL; DYES; COAGULATION/FLOCCULATION; MECHANISM; BENZENE; PH; Chemistry